2018
DOI: 10.1016/j.ajog.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The intrapartum and perinatal risks of sleep-disordered breathing in pregnancy: a systematic review and metaanalysis

Abstract: Maternal sleep-disordered breathing is associated with increased risks of adverse intrapartum and perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 61 publications
(184 reference statements)
2
62
0
3
Order By: Relevance
“…of adverse pregnancy outcomes 1,[29][30][31]. The results of our study and that of others suggest that a high ESS score is associated with intrapartum complications.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…of adverse pregnancy outcomes 1,[29][30][31]. The results of our study and that of others suggest that a high ESS score is associated with intrapartum complications.…”
supporting
confidence: 68%
“…A recent report from the UK showed that one in 20 stillbirths and neonatal deaths were related to labour . Although SDB is an established risk factor for cardiac and metabolic conditions outside of pregnancy, various systematic reviews now suggest that it is also related to a plethora of adverse pregnancy outcomes . The results of our study and that of others suggest that a high ESS score is associated with intrapartum complications.…”
supporting
confidence: 56%
“…[2][3][4] In pregnancy, OSA is associated with gestational diabetes mellitus (GDM), hypertensive disorders, preterm birth and reduced birthweight. 5 In pregnancy, pre-existing OSA can worsen, but OSA can also present de novo. 5 Multiple pregnancy is associated with many of the same adverse perinatal outcomes as OSA, including preterm birth, intrauterine growth restriction, GDM and hypertensive disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the metabolic and cardiovascular associations of SDB in the non‐pregnant population, maternal SDB has been associated with a range of adverse pregnancy outcomes including gestational diabetes, gestational hypertension and pre‐eclampsia . Adverse outcomes in the offspring of women with SDB have also been reported, including pre‐term birth and low birthweight . It is not known whether this is a direct effect of SDB or a consequence of the maternal complications associated with SDB which can influence foetal growth and timing of delivery.…”
Section: Sdb With Adverse Pregnancy Outcomes: Potential Mechanismsmentioning
confidence: 99%